Pemberdayaan Pendamping Lansia Penderita Penyakit Stroke dalam Mengingat Bacaan dan Gerakan Shalat di Sidomulyo Palangka Raya - Nur Winda Maysara; Muslimah Muslimah; Nurul Wahdah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Empowerment activities for elderly stroke sufferers in remembering reading and prayer movements aim to provide guidance and direction to the community or a family member of stroke patients to be able to find out how to provide treatment to elderly stroke sufferers who forget to read and pray movements due to the impact of stroke (post-stroke) and as an effort to form mentors who can pay attention and guide elderly stroke sufferers well, add insight to companions and so that later companions can help, accompany, and train these stroke sufferers to spur themselves and their ability to remember reading and prayer movements. The method used in this activity is the ABCD (Asset Based Community-driven Development) method. The empowerment for this supervisor is carried out with a series of activities including; (1) reflexology, (2) congregational prayer, and (3) guidance on reading and prayer movements. Through this effort, stroke sufferers are able to remember readings and prayer movements, but have a drawback, namely that they must start by mentioning the beginning of the prayer reading and cannot pray individually. In this activity, it is hoped that the companion can help stimulate the memory of the elderly with stroke to continue to assist them in remembering readings and prayer movements as well as assisting the five daily prayers.